Cotranslational Biogenesis of Membrane Proteins in Bacteria - Mercier, Evan; Wang, Xiaolin; Bögeholz, Lena A. K.; Wintermeyer, Wolfgang; Rodnina, Marina V. (Frontiers in Molecular Biosciences, 2022)
Nascent polypeptides emerging from the ribosome during translation are rapidly scanned and processed by ribosome-associated protein biogenesis factors (RPBs). RPBs cleave the N-terminal formyl and methionine groups, assist cotranslational protein folding, and sort the proteins according to their cellular destination. Ribosomes translating inner-membrane proteins are recognized and targeted to the translocon with the help of the signal recognition particle, SRP, and SRP receptor, FtsY. The growing nascent peptide is then inserted into the phospholipid bilayer at the translocon, an inner-membrane protein complex consisting of SecY, SecE, and SecG. Folding of membrane proteins requires that transmembrane helices (TMs) attain their correct topology, the soluble domains are inserted at the correct (cytoplasmic or periplasmic) side of the membrane, and – for polytopic membrane proteins – the TMs find their interaction partner TMs in the phospholipid bilayer. This review describes the recent progress in understanding how growing nascent peptides are processed and how inner membrane proteins are targeted to the translocon and find their correct orientation at the membrane, with the focus on biophysical approaches revealing the dynamics of the process. We describe how spontaneous fluctuations of the translocon allow diffusion of TMs into the phospholipid bilayer and argue that the ribosome orchestrates cotranslational targeting not only by providing the binding platform for the RPBs or the translocon, but also by helping the nascent chains to find their correct orientation in the membrane. Finally, we present the auxiliary role of YidC as a chaperone for inner-membrane proteins. We show how biophysical approaches provide new insights into the dynamics of membrane protein biogenesis and raise new questions as to how translation modulates protein folding.